Changing labour market risks in the service economy: Low wages, part-time employment and the trend in working poverty risks in Germany. (February 2019) - Brülle, Jan; Gangl, Markus; Levanon, Asaf; Saburov, Evgeny
The article presents an analysis of the development of labour market risks in Germany in light of changing working poverty risks. Low hourly wages and part-time employment are identified as the main demand-side-related mechanisms for household poverty. Their measurement and development are discussed as well as their contribution to trends in working poverty risks. A rise in low wages, especially among part-time employed households, was decisive for the increase in working poverty risks in Germany by 45% between the end of the 1990s and the end of the 2000s. We therefore study these trends more closely in the multivariate analysis. The results show that while low wages are unequally distributed across occupations and industries, shifts in employment between sectors explain only a minor part of the change in low wages. However, they reveal a polarization of low-wage risks by skill-level and sector of employment, on the one hand, and full-time and part-time employees, on the other hand.